On polynomial EPr matrices - Ar. Meenakshi; N. Anandam (International Journal of Mathematics and Mathematical Sciences)
This paper gives a characterization of EPr-λ-matrices. Necessary and sufficient conditions are determined for (i) the Moore-Penrose inverse of an EPr-λ-matrix to be an EPr-λ-matrix and (ii) Moore-Penrose inverse of the product of EPr-λ-matrices to be an EPr-λ-matrix. Further, a condition for the generalized inverse of the product of λ-matrices to be a λ-matrix is determined.